Move Analysis of Awards Acceptance Speeches in The 22nd Vodafone Ghana Music Awards Ceremony - John York-Williams; Joseph Benjamin Archibald Afful; Emmanuel Mensah Bonsu (LET: Linguistics, Literature and English Teaching Journal)
It has become a tradition that any musician who wins an award delivers a speech to acknowledge those who contributed to the award’s success. This has led to the emergence of Awards Acceptance Speeches (AASs). Despite the recent popularity of genre analysis on professional genres, AASs as a genre, have not been researched, especially in the Ghanaian context. To this end, this paper sought to examine the generic structure of the AASs of Ghanaian musicians in the 22nd Vodafone Ghana Music Awards Ceremony. 20 AASs were sampled for the study. The study adopted Swales’ (1990) approach to move analysis, focusing on the generic structure. The analysis revealed that Thanking move was the most frequent. A 6 move-structure was identified. The study concluded with implications for successful acculturation of musicians and other entertainment industry players in their discourse communities and recommendations for further studies.